Highly active RRMS and ocrelizumab after failure of alemtuzumab therapy - Vališ, Martin; Ryška, Pavel; Halúsková, Simona; Klímová, Blanka; Pavelek, Zbyšek (BMC neurology, 2020)
BACKGROUND: A high multiple sclerosis activity while on alemtuzumab is rather uncommon compared to moderate-efficacy drugs. The purpose of this case report is to present a case of a 37-year-old female patient with bronchial asthma and no other medical history, whose disease activity required switching from dimethyl fumarate to fingolimod, then to alemtuzumab and finally to ocrelizumab. CASE PRESENTATION: In our patient, two severe attacks were observed and treated after administration of the first pulse of alemtuzumab. After six months of therapy, patient's immunological profile showed the expected decrease in CD4+ and CD8+ T-cells and, markedly increased values of CD19+ B-cells. Surprisingly memory B-cells, which typically repopulate very slowly following alemtuzumab treatment, were above baseline levels. Regular administration of ocrelizumab based on a standardised scheme, after the alemtuzumab therapy failure, resulted in the stabilisation of the patient's condition both clinically and radiologically. CONCLUSION: Thus, when the alemtuzumab treatment is unsuccessful, the authors recommend testing T- and B-cell levels and proceeding with an early switch to ocrelizumab if high B-cell counts are found.
Keywords: Treatment failure; alemtuzumab; Humans; Lymphocytes; Disease progression; Female; Relapse; dospělí; lidé; humanizované monoklonální protilátky; CD8-Positive T-Lymphocytes; B-lymfocyty; CD8-pozitivní T-lymfocyty; Adult; Multiple sclerosis; Antibodies, Monoclonal, Humanized; Multiple Sclerosis, Relapsing-Remitting; ženské pohlaví; relabující-remitující roztroušená skleróza; CD4-Positive T-Lymphocytes; B-Lymphocytes; CD4-pozitivní T-lymfocyty; Alemtuzumab; Treatment Failure; Case report; Ocrelizumab; neúspěšná terapie